Strategi Marketing Public Relations Jawa Timur Park Group dalam Menjalin Good Relations dengan Stakeholders - Rachmad Rinata, Asfira; Sariniati, Mina (Unitri Press, 2020)
The purpose of this research is to know the planning strategy of public relations Jawa Timur Park Group especially the strategy to establish good relationships with its stakeholders and support programs with the good relations. This research uses a qualitative paradigm by colaborating data from semi-structured interviews and documentation. The concepts used in his analysis are public relations planning strategies initiated by Cutlip, Center, and Broom, including making decisions about objectives and objectives, identifying deciding audiences, setting policy or strategy rules, and deciding which strtegi to use. The results of this research marketing public relations Jawa Timur Park Group made decisions that were handed over entirely to the leader of the company. Public relations also makes the purpose of the program to attract stakeholders so that they want to cooperate. In addition to identifying the audience by looking at what is their characteristic, the company has a policy or strategy rule that is to promote the understanding of the East Java park group company to all its business scopes, and decide what strategy the company will use. The strategy that has been decided in establishing relationships with East Java Park Group stakeholders is implemented through programs tailored to stakeholders' relationships. These programs are Corporate Social Responsibility (CSR), special events, discounts, and additional facilities.